An Interesting Lycoperdon affin to L. ericaeum - Martín Esteban, María Paz; Jeppson, Mikael (Revista Catalana de Micologia, 2007)
An interesting Lycoperdon affin to L. ericaeum. Lycoperdon collections recorded fromacidic, dry, mossy habitats on rocks or on sand in Fennoscandia and the Northeastem of Spain are heredescribed. These collections are close to L. ericaeum but differs in its protruding ostiole and its subelastic capillitium.